MAPPING IN VITRO AND IN VIVO DERIVED CYP2C9 AND CYP2C19 ONTOGENY FUNCTIONS: A CRITICAL COMPARISON BETWEEN VARIOUS ONTOGENY MODELS. Issue 1 (14th December 2015) - Salem, Farzaneh; Johnson, Trevor; Rostami-Hodjegan, Amin
Abstract : In vivo derived ontogeny profiles for CYP1A2 and CYP3A4, show improved clearance (CL) predictions within a paediatric physiologically based pharmacokinetic (p-PBPK) model1. The aim of this study is to derive ontogeny functions (OF) for CYP2C9 and CYP2C19 based on age related CL data on ibuprofen and pantoprazole & lansoprazole, respectively. A literature review was undertaken to collect age related CL data for these probes, the values were deconvoluted back to intrinsic CL values (per mg of liver microsomal protein) as described previously. The 'best-fit' algorithm for ratio of paediatric to mean adult intrinsic CL with age was determined in Graphpad Prism5 to obtain in vivo OF for CYP2C9 and CYP2C19. These were compared for performance with previously established 'in vitro' OF in Simcyp Paediatric simulator (v14) using validation datasets. CYP2C9 and CYP2C19 enzyme activities showed an increase with age to values higher than adults by ages 2 and 1 month respectively, maximum values were reached at 1.5 years and 6 months, respectively before declining to typical adult levels by around 25 years. The CYP2C9 in vivo derived OF led to improved predictions of diclofenac and S-Warfarin CL compared to in vitro derived OF across the age range. For CYP2C19 there is a dearth of suitable validation compounds due to lack of clinical data with a possibility of using omeprazole or voriconazole. The reasons for discrepancy between in vitro and in vivo derived OF require further investigation.